Tractor - Sirett, Dawn; Gardner, Charlie; Harvey, Victoria; Harvey, Victoria; Palastaga, Victoria (London Dorling Kindersley Limited, 2011)
Invites young readers to feel the textures of such things associated with a tractor as a wheel, trailer, lights, tracks, chunky tires, and a shiny hood. On board pages
Picture book
1 2 13 23
Keywords: Picture book for children